The pattern of health-seeking behavior among juang tribe- a particularly vulnerable tribal group of Odisha, India - Kaberi Sahoo; Soumya R Nayak; Priyanka Khurana (Wolters Kluwer Medknow Publications, 2023)
Introduction: Social and economic position, environment, access to healthcare, ethos, and worldview are all important determinants of people's health-seeking behavior. Tribal communities in India oscillate between their emic rationale for the cause and treatment of health concerns on the one hand and affordable modern methods on the other. The present article is based on a study conducted among the Junag tribe of Odisha to understand their acceptance and preference for traditional or modern healthcare systems and the reasons for these choices. Material and Methods: Purposive sampling, a pre-structured schedule, an observation approach, case studies, and interviews with community members have been used to gather the primary data used in the study. Result: The study identified a diverse pattern of health-seeking behavior. From the four villages, 70% of respondents combined into cluster-1 preferred the traditional healthcare system, mostly for geographical and cultural reasons, as opposed to 95% of respondents from the villages in cluster-2, who preferred modern healthcare services because they were more easily accessible and involved modern healthcare providers. Conclusion: In this research work, it has been found that the Juang tribe is in a transitional phase and uses a hybrid approach to health seeking. Moreover, it has also been discovered that important variables including cultural attitudes and the affordability of contemporary healthcare services have influenced people's decisions toward healthcare systems.